Grammatikalisering af danske præpositioner - Boye, Kasper; Messerschmidt, Maria; Straube Hansen, Josefine; Schaffalitzky de Muckadell, Victoria (Ny forskning i grammatik, 2019)
Messerschmidt & al. (2018) made a distinction between grammatical and lexical prepositions based on the functional theory of grammatical status in Boye & Harder (2012), and demonstrated that this distinction is significant for the description of agrammatic speech. The functional theory predicts that grammatical items attract less attention than lexical ones. In this paper, we use a letter detection experiment to demonstrate that this also holds for Danish prepositions. Not all grammatical-lexical preposition pairs contrasted show a significant difference between letter detection rates, however. We argue that varying degrees of differences reflect different positions in a grammaticalization cline in which a grammatical descendent is gradually distilled out of a lexical source.